2017
DOI: 10.1167/iovs.17-22030
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Circulating Omentin-1 on the Retinal Circulation in Patients With Type 2 Diabetes Mellitus

Abstract: Increased concentrations of plasma omentin-1 might be linked to elevated RBF levels probably through elevated blood velocity in patients suffering from type 2 diabetes with incipient DR, especially in female patients, which warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Korany et al (23) also found that, serum omentin-1 level was significantly lower in diabetic patients compared with the control, and in DR compared with diabetics without DR. Omae et al (24) also found that, serum omintin-1 was reduced significantly (P<0.001) in DR patients, comparing with DM patients without retinopathy. Additionally, in recent meta-analysis study showed that serum level of omentin was significantly lower in T2DM compared to healthy controls (25) .…”
Section: Discussionmentioning
confidence: 84%
“…Korany et al (23) also found that, serum omentin-1 level was significantly lower in diabetic patients compared with the control, and in DR compared with diabetics without DR. Omae et al (24) also found that, serum omintin-1 was reduced significantly (P<0.001) in DR patients, comparing with DM patients without retinopathy. Additionally, in recent meta-analysis study showed that serum level of omentin was significantly lower in T2DM compared to healthy controls (25) .…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, it was revealed that the serum omentin-1 level was significantly lower in diabetic patients compared to controls and in diabetics with DR compared to diabetics without DR (Abdelraouf Korany et al, 2018). Additionally, it was found that serum omentin-1 levels were considerably lower in DR patients compared to DM patients without retinopathy (Omae et al, 2017). Additionally, recent metaanalysis research found that T2DM patients had significantly lower serum omentin-1 levels than healthy controls (As, 2019).…”
Section: Relation Of Serum Omentin-1 With Diabetic Retinopathymentioning
confidence: 99%
“…If both eyes had equal retinopathy, one eye was randomly assigned to the study. Patients with other ocular disease, such as glaucoma or retinal vessel occlusion, a history of laser treatment or intraocular surgery, moderate-to-severe cataract, previous ocular inflammation, clinically significant macular edema, and moderate-to-high refractive error (± >3.0 D) were excluded [14,15].…”
Section: Subjectsmentioning
confidence: 99%